Dynamic flexural behavior of AR-glass textile reinforced concrete under low-velocity impact loading. Issue 1 (2nd January 2023) - Li, Anling; Guo, Shuaicheng; Mobasher, Barzin; Zhu, Deju
Abstract : Textile reinforced concrete (TRC) has a higher sustainable potential than conventional reinforced concrete, with a significantly lower CO2 footprint. To study the dynamic flexural behavior of TRC composites, the Alkali Resistant (AR)-glass textile reinforced concrete (TRC) plate specimens was investigated with the three-point bending test under low-velocity impact. This study examined the influences of the textile layer number (1, 2, and 3 layers) and the impact velocity (1.29–4.04 m/s) on the dynamic behavior of TRC composites, and compared that with the quasi-static test results. The results show that the Young's modulus and initial peak impact stress of the AR-glass TRC generally increase with the impact velocity, while its influence on the ultimate flexural stress is insignificant. It is found that the ultimate flexural stress can better represent the dynamic flexural capacity of AR-glass TRC materials than the initial peak stress. The failure modes were also analyzed in terms of crack patterns and crack widths, which were measured through the digital image correlation (DIC) method. It was found that rebound and rupture are the two main failure scenarios of the AR-glass TRC under low-velocity impact loading. The cracks of AR-glass TRC specimens could be mainly categorized into flexural crack, shear-flexural crack, and interfacial debonding crack. The study of stress-crack width relationship is helpful to determine the design strength of TRC material to meet the requirement on crack width.